Transforming mosque sustainability: leveraging Islamic economics and finance for community empowerment - Hidayat, Rahmat; Rodoni, Ahmad; Sukardi, Budi; Fachrurazi, Fachrurazi; Asmanto, Eko; Ismail, Nurizal (Fakultas Ekonomi dan Bisnis Islam, 2025)
This research focuses on the shift in mosque empowerment models, particularly in terms of financial sustainability, rooted in Islamic economics and finance. By exploring the correlation of Islamic economics (Y), Islamic finance (Y), and mosque sustainability (Z), this research can utilize the mixed method approach of quantitative analysis to survey 200 congregation members, conduct in-depth interviews with five key informants, and employ PLS-SEM. This is the first mosque sustainability performance study to provide a quantitative analysis, along with PLS-SEM, and to correlate finance and economics in the Islamic context. Findings indicate that Islamic finance intermediates the influence of Islamic economics on mosque sustainability (indirect β=0.527; p<0.001). Islamic economics is explained to have a considerable direct influence on Islamic finance (β=0.782; p<0.001) as well as Islamic finance being the greatest contributor to mosque sustainability (β=0.673; p<0.001). This research affirms the four-dimensional sustainability pillar and the anticipation of mosque management to respond to the SDGs. This provided strong financial governance, partnership with Islamic banking, trained financial governance, and Islamic financial literacy courses